Comparison between Endoscopic and External Dacryocystorhinostomy by Using the Lacrimal Symptom Questionnaire: A Pilot Study. Issue 1 (January 2018) - Wong, Wai Keat; Dean, Simon; Nair, Salii
Background: Epiphora has a significant impact on the patient's quality of life and is commonly caused by nasolacrimal duct obstruction. Dacryocystorhinostomy (DCR) has traditionally been performed via an external approach, which involves a skin incision. With the advent of endoscopes, the endonasal approach to DCR has gained significant popularity. Method: To prospectively compare the quality of life of adult patients who underwent either an endonasal or an external DCR for acquired nasolacrimal duct obstruction, the Lacrimal Symptom Questionnaire (Lac-Q) was administered before and after surgery. The treatment group assignment was nonrandom and performed based on patient preference. The Lac-Q is a validated questionnaire that assesses the subjective perception of one's well-being from an eye-specific symptom and social impact standpoint. Total scores range from 0 (no concerns) to 33 (maximal degree of ocular symptoms and social impact). Results: Sixty patients (22 in the endonasal group, 38 in the external group) were recruited between January 1, 2014, and January 1, 2016. Postoperative assessment was performed at 3 and 6 months. Patients who underwent external DCR reported a median 7.0–point improvement (interquartile range [IQR], 3.0–11.0) in total Lac-Q scores. A 12.0–point improvement (IQR, 10.0–18.5) was seen in the endonasal group (p = 0.005). The median change in the social impact score was 3.0 and 4.0 in the external group and the endoscopic group, respectively (p = 0.029). Changes in the median lacrimal symptom score were 4.0 in the external group and 8.0 in the endoscopic group (p = 0.014). The anatomic patency rate was lower in the external group (60.0%) when compared with the endonasal group (90.4%). Patients in the external DCR group were significantly older (median age, 51 versus 41 years). Conclusion: Our study indicated that both endonasal and external DCR can lead to improvement in quality of life by using a validated questionnaire. Although there are differences in age and anatomic success rates between the two groups, subgroup analyses indicated that the differences in the Lac-Q scores persisted when age and anatomic patency were removed as potential confounding factors. Further larger, randomized studies would be helpful.